2017
DOI: 10.12991/marupj.300329
|View full text |Cite
|
Sign up to set email alerts
|

Cellular toxicity and biological activities of honey bee (Apis mellifera L.) venom

Abstract: Bee venom (BV) has been suggested as an apitherapy tool to be considered for various diseases including cancer. However, the mechanisms action of BV and its toxicity on tumorigenic and nontumorigenic cells are poorly understood. Here, we investigated the antiproliferative, cytotoxic and antibacterial activities of honey bee (Apis mellifera L.) venom on nontumorigenic cells, several tumor cell lines and multidrug resistant human pathogens (MDRP) such as Extended Spectrum Beta-Lactamases producing Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Despite the convincing data regarding the potential use of BV, more specifically melittin, against a variety of cancer types, its applicability to humans remains very challenging because of its non-specific cytotoxicity [80]. Current optimization methods are focusing on nanoparticle-based delivery of melittin in order to avoid such problems.…”
Section: Bioactivities and Therapeutic Applications Of Bee Venom Amentioning
confidence: 99%
“…Despite the convincing data regarding the potential use of BV, more specifically melittin, against a variety of cancer types, its applicability to humans remains very challenging because of its non-specific cytotoxicity [80]. Current optimization methods are focusing on nanoparticle-based delivery of melittin in order to avoid such problems.…”
Section: Bioactivities and Therapeutic Applications Of Bee Venom Amentioning
confidence: 99%
“…These allergic reactions can be categorized to be mild and restricted to the skin or moderate to severe with a risk of life-threatening anaphylaxis. Although there are many convincing results regarding the potential use of bee venom, more specifically melittin, against various types of cancer, its applicability to humans remains very challenging owing to its non-specific cytotoxicity [85].…”
Section: Allergy Testing Directions For Patients and Contraindicationsmentioning
confidence: 99%
“…Modern pharmacological studies showed that in vitro and in vivo, BV has antibacterial effects against bacteria, viruses, and fungi (El-Seedi et al 2020). However, the use of B.V. has shown adverse effects on normal cells as reported by Gülmez et al (2017), Cherniack and Govorushko (2018). Thus, there is still a need for more studies that can eliminate or even decrease the cytotoxic effect of B.V. and enhance its therapeutic effect in the target organ.…”
Section: Introductionmentioning
confidence: 99%